Analisis Peran Pemangku Kepentingan Dalam Pengelolaan Rehabilitasi Hutan Daerah Aliran Sungai (DAS) Desa Beka Kecamatan Marawola Kabupaten Sigi - Bakri, Wiranti R; Golar, Golar; Maiwa, Arman (Savana Cendana, 2024)
Damage to watersheds (DAS) in many locations in Indonesia currently requires attention. Increasing pressure from population growth, urbanization, shrinking watersheds (DAS) and the expansion of critical areas and regional development have caused an increased risk of flooding, landslides and drought. Similar conditions also occur in the Beka Village River Watershed (DAS). This research aims to analyze the role of stakeholders in managing the rehabilitation of river basin (DAS). This research method uses purposive sampling and snowball sampling to determine the role of stakeholders and stakeholder analysis in managing river watershed (DAS) forest rehabilitation. Conducted through interpretation of the matrix of influences and interests in the management if River Basin (DAS) forest rehabilitation, 9 stakehokholders have been identified who have roles ranging from forest management, community empowerment and supervision. The identified stakeholders consist of government and community elements involved in the process. By identifying the role of stakeholders, analyzing the 4Rs and assessing the level of influence of their intersts, it can be seen that collaboration between stakeholders is the main key to achieving the goal of watershed forest rehabilitation management. The synerghy between various parties such as BPDAS Palu Poso and KPH Kulawi provides a solid foundation for optimizing the management potential of Beka Village Watershed Forest Rehabilitation (DAS).